Pharmacokinetic comparison of a fixed-dose combination versus concomitant administration of amlodipine, olmesartan, and rosuvastatin in healthy adult subjects - Oh, Minkyung (Drug Des Devel Ther, 2019)
Objective: The aim of this study was to compare the pharmacokinetic (PK) and safety profiles of a fixed dose combination (FDC) formulation and co-administration of amlodipine, olmesartan, and rosuvastatin. Materials and methods: This study was an open-label, randomized, cross-over design conducted in healthy male volunteers. All subjects received either a single FDC tablet containing amlodipine 10 mg/olmesartan 40 mg/rosuvastatin 20 mg, or were co-administered an FDC tablet containing amlodipine 10 mg/olmesartan 40 mg and a tablet containing rosuvastatin 20 mg, for each period, with 14-day washout periods. Plasma concentrations of amlodipine, olmesartan, and rosuvastatin were measured by liquid chromatography tandem mass spectrometry. Safety was evaluated by measuring vital signs, clinical laboratory parameters, physical examinations, and medical interviews. Results: Sixty-four subjects were enrolled, and 54 completed the study. The geometric mean ratios and 90% CI for the maximum plasma concentration (C(max)) and area under the curve from time zero to the last sampling time (AUC(t)) were 1.0716 (1.0369,1.1074) and 1.0497 (1.0243,1.0757) for amlodipine, 1.0396 (0.9818,1.1009) and 1.0138 (0.9716,1.0578) for olmesartan, and 1.0257 (0.9433,1.1152) and 1.0043 (0.9453,1.0669) for rosuvastatin. Fourteen cases of adverse events occurred in 12 subjects. There was no statistically significant clinical difference between the formulation groups. Conclusion: The 90% CI of the primary PK parameters were within the acceptance bioequivalence criteria, which is ln (0.8) and ln (1.25). These results indicate that the FDC formulation and co-administration of amlodipine, olmesartan and rosuvastatin are pharmacokinetically bioequivalent and have similar safety profiles.